Therapeutic Targeting of DNA Damage Response Pathways in TP53 - and ATM -Mutated Tumors - Shim, Ye Jee (Brain tumor research and treatment, 2025)
Mutations in tumor protein p53 ( ) and ataxia telangiectasia mutated ( ) genes are frequently observed across various solid and hematologic malignancies and are associated with genomic instability, treatment resistance, and poor clinical outcomes. These alterations compromise the G1/S cell cycle checkpoint and increase cellular dependence on compensatory DNA damage response (DDR) pathways, including the ataxia telangiectasia and Rad3-related protein kinase (ATR)-checkpoint kinase 1 (CHK1)-WEE1 G2 checkpoint kinase (WEE1) axis. This has led to the development of DDR-targeted therapies that exploit synthetic lethality in tumors with TP53 or ATM dysfunction. Inhibitors targeting ATM, ATR, CHK1, and WEE1 have all shown encouraging activity in early-phase clinical trials, particularly in biomarker-enriched subgroups. Poly(ADP-ribose) polymerase (PARP) inhibitors-originally approved for -mutated breast cancers-are now being evaluated in - or -deficient tumors, often in combination with other DDR-targeting agents to enhance efficacy. Clinical trials increasingly support the efficacy of DDR inhibitors in biomarker-defined DDR-deficient tumors, specifically beyond mutations. This review summarizes current understanding of DDR-targeted strategies in - and -mutant cancers, with an emphasis on relevant clinical data and ongoing trials. Expanding the clinical use of DDR inhibitors based on molecular profiles may provide new therapeutic options for genomically unstable tumors across adult and pediatric populations.